EVALUATION OF HAEMATOLOGICAL PARAMETERS IN MALARIA INFECTION AND ITS ASSOCIATION WITH DIFFERENT SPECIES OF MALARIAL PARASITE - Ali Hyder (Army Medical College Rawalpindi, 2020)
Objective: To determine the association of various haematological parameters with different species of malarial parasites.